Pengembangan Teknologi Tepat Guna Untuk Produksi Bioetanol Skala Komunitas. Studi Kasus Pemanfaatan Rumput Laut Sargassum Sp. di Gunungkidul, Yogyakarta. - Eko Setiawan; Muh Arif Wibisono; Ferry Ikhsandy (REACTOR: Journal of Research on Chemistry and Engineering, 2026)
Seaweed (Sargassum sp.) in Gunungkidul has potential as a third-generation bioethanol feedstock, but its development remains constrained by low conversion efficiency and reliance on laboratory-scale equipment. This study examines bioethanol production using an appropriate technology approach with equipment available in domestic market and evaluates the effect of HCl (1-5%) and silicone antibfoam addition (0.07-0.14% w/v) on the stability of the hydrolysis process. The experimental results showed that hydrolysis without antifoam produced uncontrollable foam with material loss up to 16%. Antifoam addition successfully controlled the foam, reduced loss to 5%, and increased Brix to 6-8%. Field measurements with a refractometer showed ethanol content of 22% (v/v), but laboratory verification using gas chromatography (GC) revealed ethanol content of 0.09% and total sugar in dried seaweed of 0.04%, far below literature values. This discrepancy proves that the refractometer overestimation is due to dissolved solids interference. Additionally, during the hydrolysis process, corrosion on SS304 and Cl2 gas were identified, requiring pH neutralization mitigation and scrubber system. Solid waste from fermentation has potential as an organic fertilizer mixture with water content of 91.35%, C-Organic of 0.975%, Total N of 0.07%, K₂O of 0.565%, and P₂O₅ of 0.070%. Integration with downstream industries such as the alginate industry (HCl 3% scenario) save consumption NaOH by 35,63% and HCl by 14,36%. This study concludes that appropriate technology framework is feasible for replication at the community scale, however, pretreatment optimization on raw material and standardized testing validation needs to be established and controlled.